Enterprise heterogeneity, agglomeration model, and urban exports: Evidence from Chinese cities and micro enterprises. Issue 8 (17th November 2021) - Zhang, Wenwu; Li, Ruru; Zuo, Fei
Abstract : Heterogeneous enterprise agglomeration is an important perspective in understanding urban exports and reshaping the new advantages of urban openness. This paper considers data from China's industrial enterprises and municipality-level panel data from 192 cities to systematically examine enterprises' heterogeneity, agglomeration patterns, and urban exports. The results reveal that: (1) the heterogeneity in enterprise productivity exhibits a significant promotional effect on urban exports in China's central and northeastern regions, but not on its western regions; (2) specialized agglomeration positively affects exports in the central and western regions and in small and medium-sized cities, while diversified agglomeration significantly and positively impacts the eastern and northeastern regions and small and large cities; and (3) thresholds exist in determining the effects of agglomeration and sequencing on urban exports and their sequence by considering heterogeneity in enterprises' productivity. This work provides important policy implications for the development of export trade in cities and countries by suggesting a focus on rational planning and adjustments to regional industrial policies, improvements to talent flow mechanisms, and construction of social infrastructures. HIGHLIGHTS Heterogeneous enterprise agglomeration can shape exports from city-based businesses A new simultaneous model determines how to increase urban exports Heterogeneity can have various impacts in different Chinese regions and cities Increasing productivity and exports requires strategic planning for optimization